3D Self‐Supported Visible Light Photochemical Nanocatalysts - Fateh Mikaeili; Mohammad Mahafuzur Rahaman; Pelagia‐Irene (Perena) Gouma (Advanced Science)
Abstract This work focuses on 3D, self‐supported, nanofibrous TiO2 structures (nanogrids) prepared using blend electrospinning. The presence of anatase and brookite phases in Cu‐doped TiO2 nanogrids significantly enhances the photocatalytic properties of the titania system. The absorption edge in Cu‐doped TiO2 shifts to the visible due to the narrowed bandgap and efficient separation of photogenerated charge carriers facilitated by Cu doping. The presence of the brookite phase further contributes to the enhanced performance, by reducing electron–hole recombination. A wide range of characterization techniques, including cyclic voltammetry and chronoamperometry studies which show that the Cu doped TiO₂ sample generates a significant photocurrent under visible light, are employed to elucidate the role of Cu doping in enhancing the visible light photocatalytic efficiency of TiO2 nanogrids, offering valuable insights for developing advanced photochemical catalysts for environmental and energy applications. The nanogrids studied here are far superior to P25 Degussa and are activated by natural sunlight and do not require a filtration system to remove nanoparticles from the water. These self‐supported nanofibrous photochemical catalysts offer all the benefits of nanomaterials while suffering from none of their drawbacks.